Structural Analysis with Finite Elements - Hartmann, Friedel; Katz, Casimir; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
Structural Analysis with Finite Elements, 2nd Edition provides a solid introduction to the foundation and the application of the finite element method in structural analysis. It offers new theoretical insight and practical advice on why finite element results are 'wrong,' why support reactions are relatively accurate, why stresses at midpoints are more reliable, why averaging the stresses sometimes may not help or why the equilibrium conditions are violated. This second edition contains additional sections on sensitivity analysis, on retrofitting structures, on the Generalized FEM (X-FEM) and on model adaptivity. An additional chapter treats the boundary element method, and related software is available at www.winfem.de.
What are finite elements? -- What are boundary elements? -- Frames -- Plane problems -- Slabs -- Shells -- Theoretical details.
Keywords: Buildings—Design and construction; Building; Construction; Engineering, Architectural; Mechanics; Mechanics, Applied; Computational intelligence; Civil engineering; Building Construction and Design; Solid Mechanics; Computational Intelligence; Civil Engineering